Improving Early Children's Language Capabilities through Interactive Compact Disk Media - Ansorida (Journal of Childhood Development, 2022)
Language skills are essential skills to be developed from an early age. That's because language is an important means in human life to communicate. With language, humans can issue ideas and opinions to establish communication with other humans. Thus, language skills should have been improved since early childhood. In line with the development of science and technology, various kinds of learning media can be found that can be used to develop students' abilities, one of which is interactive compact disk media. The research was conducted at Raudhatul Athfal Al-Hikmah Kedaton Bandar Lampung. This research is a Classroom Action Research with a qualitative descriptive type. The data collection technique that the researcher uses is the observation method as the primary method, the documentation method as support in research, and the interview method to determine the extent of the teacher's response to the use of interactive compact disk media in improving children's language skills. The results of this study that interactive compact disk media can improve children's language skills in Raudhatul Athfal Al-Hikmah Kedaton Bandar Lampung with very satisfying results. This can be seen from the development of students in the pre-cycle research it is known that students who reach the assessment standard develop according to expectations. There are only 3 children out of all 15 students. Then in the first cycle, the number of children who had the language skills as expected increased to 9 children, and in the second cycle, it rose again to 12 students or 80% of the students had reached the assessment standards that had been set.